2020
DOI: 10.3390/cells9020382
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of the Astrocyte Syncytium Differentially Affects AQP4 Isoforms

Abstract: The water channel protein aquaporin-4 (AQP4) and the gap junction forming proteins connexin-43 (Cx43) and connexin-30 (Cx30) are astrocytic proteins critically involved in brain water and ion homeostasis. While AQP4 is mainly involved in water flux across the astrocytic endfeet membranes, astrocytic gap junctions provide syncytial coupling allowing intercellular exchange of water, ions, and other molecules. We have previously shown that mice with targeted deletion of Aqp4 display enhanced gap junctional coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…AQP4ex also regulates water transport at the BBB level, and binds with human neuromyelitis optica autoantibody that is associated with autoimmune demyelinating diseases in the central nervous system [67]. In addition, the deletion of gap junction forming proteins connexin-43 (Cx43) and connexin-30 (Cx30) increases AQP4a (M1) and AQP4ex isoform levels, but reduces AQP4c (M23) isoform in astrocytes [68]. Considering these reports, further studies are needed to validate AQP4 isoforms affected by 67LR functions in astroglio-vascular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…AQP4ex also regulates water transport at the BBB level, and binds with human neuromyelitis optica autoantibody that is associated with autoimmune demyelinating diseases in the central nervous system [67]. In addition, the deletion of gap junction forming proteins connexin-43 (Cx43) and connexin-30 (Cx30) increases AQP4a (M1) and AQP4ex isoform levels, but reduces AQP4c (M23) isoform in astrocytes [68]. Considering these reports, further studies are needed to validate AQP4 isoforms affected by 67LR functions in astroglio-vascular interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Dual knock‐out of Cx30 and Cx43 uncouples astrocytes in the hippocampus, reduces water transport across astrocytic plasma membranes, and increases the leakiness of the BBB upon shear stress (Ezan et al, 2012; Lutz et al, 2009). This dual knock‐out is accompanied with the partial loss of β‐dystroglycan and Aqp4M23 (but not Aqp4M1 and Aqp4ex) (Ezan et al, 2012; Katoozi et al, 2020). Taken individually, each astroglial connexin has very distinct functions at the gliovascular interface.…”
Section: Key Components Of the Molecular Repertoire In Perivascular Amentioning
confidence: 99%
“…In addition to the effect of endothelial cell expression on astrocyte expression, the finding in Figures 1 , 2 indicating decreasing expression of AQP4 across passage number, mean that verification of AQP4 expression level will be important for future use of the immortalized astrocyte lines described here. Future studies that examine the effect of Cx43 expression and functional outcomes will need to test the level and cellular localization of AQP4 because a direct interaction between Cx43 and AQP4 has been shown in past research ( Rash and Yasumura, 1999 ; Nicchia et al, 2005 ; Katoozi et al, 2017 , 2020 ). Prior studies have shown that IL-1β, IL-1α, NFκB, and other factors produce important changes to gene expression, morphology and GJ connectivity in vivo and in primary astrocyte cultures.…”
Section: Discussionmentioning
confidence: 99%